2013
DOI: 10.1007/s10519-013-9583-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of the Neuronal Substrates for Drug Tolerance in Drosophila

Abstract: Physical dependence on alcohol and anesthetics stems from neuroadaptive changes that act to counter the effects of sedation in the brain. In Drosophila, exposure to either alcohol or solvent anesthetics have been shown to induce changes in expression of the BK-type Ca2+- activated K+ channel gene slo. An increase in slo expression produces an adaptive modulation of neural activity that generates resistance to sedation and promotes drug tolerance and dependence. Increased BK channel activity counteracts the sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Although we did not measure Clock expression in the SCN, others have shown that the SCN is responsive to ethanol (Chen et al, 2004;Prosser and Glass, 2009;. Studies in different species have illustrated that circadian clock neurons are important for alcohol tolerance and that alcohol can modulate circadian phase-shifting (Brager et al, 2010;Ghezzi et al, 2013;McElroy et al, 2009;Prosser and Glass, 2009;Ruby et al, 2009;. In this study, animals consumed far less alcohol (and for a shorter period of time) than the study by Chen et al (2004), showing chronic ethanol liquid diet alters SCN rPer2 gene expression or the study by , showing chronic (no choice) ethanol consumption alters circadian activity rhythms; thus, we would not have expected changes in circadian gene expression in the SCN or altered circadian rhythms with this paradigm.…”
Section: Discussionmentioning
confidence: 92%
“…Although we did not measure Clock expression in the SCN, others have shown that the SCN is responsive to ethanol (Chen et al, 2004;Prosser and Glass, 2009;. Studies in different species have illustrated that circadian clock neurons are important for alcohol tolerance and that alcohol can modulate circadian phase-shifting (Brager et al, 2010;Ghezzi et al, 2013;McElroy et al, 2009;Prosser and Glass, 2009;Ruby et al, 2009;. In this study, animals consumed far less alcohol (and for a shorter period of time) than the study by Chen et al (2004), showing chronic ethanol liquid diet alters SCN rPer2 gene expression or the study by , showing chronic (no choice) ethanol consumption alters circadian activity rhythms; thus, we would not have expected changes in circadian gene expression in the SCN or altered circadian rhythms with this paradigm.…”
Section: Discussionmentioning
confidence: 92%
“…Our understanding of the role of the central complex in ethanol behaviors is still rudimentary, however, specific classes of ellipsoid body neurons are important for ethanol-induced hyperactivity and ethanol sedation tolerance [14] , [67] , [68] . The mushroom bodies promote ethanol-induced hyperactivity, ethanol preference, ethanol reward, and recovery from sedation induced by the related benzyl alcohol [21] , [27] , [67] , [69] , [70] . Functional mapping of the mushroom body for ethanol behaviors, while still preliminary, suggests the use of specific neuropils for simpler behaviors, and sequential use of distinct neuropils for more complex behaviors.…”
Section: Dopamine and Drugs Of Abusementioning
confidence: 99%
“…Many studies over the years have established the fruit fly Drosophila melanogaster as a non-conventional but very relevant model to explore molecular mechanisms underlying drug response. These have mostly focused on ethanol, modeling early stages of ethanol exposure, including its immediate locomotor effects (reviewed extensively in Rodan and Rothenfluh, 2010 ; Kaun et al, 2012 ; Devineni and Heberlein, 2013 ; Ghezzi et al, 2013a ), its hedonic value, as reflected by voluntary consumption (Devineni and Heberlein, 2009 ), and the formation of long-lasting memories for the rewarding experience (Kaun et al, 2011 ; Figure 1 ). This review will present recent progress in which fruit flies were used to uncover genetic and environmental elements that influence the likelihood of progressing from initial exposure to repeated drug use.…”
Section: Introductionmentioning
confidence: 99%